Raman Spectra of PbTe- and GeTe-Based Monocrystalline Epitaxial Layers - N. Romcevic; B. Hadzic; P. Dziawa; T. Story; W. D. Dobrowolski; M. Romcevic (Journal of Spectroscopy)
Lead telluride and germanium telluride are well-known IV-VI semiconductors, which is now the focus of research due to the perspective of application as thermoelectrics for midrange temperatures. Solid solutions and heterostructures on this basis, obtained by molecular beam epitaxy, are a promising direction for the development of these materials. In this paper, we have focused on the Raman spectra excited by the 514.5 nm laser line (out of resonance) of PbTe, GeTe, (Pb, Ge)Te, and (Pb, Ge, Eu)Te layers grown on BaF2 (111) monocrystalline substrates. The obtained phonon properties are related to the properties of the corresponding bulk materials or can be explained by a model that takes into account the difference in the masses of the constituent elements only, as is the case with the local mode of Ge in PbTe (registered at about 181 cm−1). Multiphonon processes registered for this phonon are a consequence of the change in the electronic structure of PbTe and electron-phonon interaction. An improvement in the quality of thin films due to doping with Eu ions was also registered.